Detection of saponin in underutilized Indonesian Sapindaceae at Cibodas Botanic Gardens - Risha Amilia Pratiwi; Yati Nurlaeni (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2022)
.